Distributional Effect of Insurer Competition on Premiums: Evidence From the Employer‐Sponsored Health Insurance Market - Haizhen Lin; Yaying Zhou (The RAND Journal of Economics, 2026)
ABSTRACT We study how insurer competition affects premiums for fully‐insured plans in the employer‐sponsored health insurance market. By utilizing quasi‐experimental variations induced by mergers among national insurers, we show that increased insurer concentration leads to higher premiums, but there exists substantial heterogeneity. In particular, we find that a increase in insurer concentration increases premiums for mid‐sized firms by but reduces premiums for large firms by . We explore additional sources of heterogeneity to shed light on the underlying mechanisms and conclude by discussing policy implications.